Foam rolling for delayed-onset muscle soreness and recovery of dynamic performance measures - Pearcey, G. E. P.; Bradbury-Squires, D. J.; Kawamoto J.-E.; Drinkwater, E. J.; Behm, D. G.; Button, D. C. (Journal of Athletic Training, 2015)
Context: After an intense bout of exercise, foam rolling is thought to alleviate muscle fatigue and soreness (ie, delayed-onset muscle soreness [DOMS]) and improve muscular performance. Potentially, foam rolling may be an effective therapeutic modality to reduce DOMS while enhancing the recovery of muscular performance.